2021
DOI: 10.1093/nar/gkab535
|View full text |Cite
|
Sign up to set email alerts
|

Recombination machinery engineering facilitates metabolic engineering of the industrial yeast Pichia pastoris

Abstract: The industrial yeast Pichia pastoris has been harnessed extensively for production of proteins, and it is attracting attention as a chassis cell factory for production of chemicals. However, the lack of synthetic biology tools makes it challenging in rewiring P. pastoris metabolism. We here extensively engineered the recombination machinery by establishing a CRISPR-Cas9 based genome editing platform, which improved the homologous recombination (HR) efficiency by more than 54 times, in particular, enhanced the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
140
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(144 citation statements)
references
References 66 publications
2
140
2
Order By: Relevance
“…Tong, Y. et al developed a CRISPR system for actinomycete genomes that can efficiently and reversibly control target genes actIORF1 and actVB [ 80 ]. Cai, P. et al, edited Pichia pastoris genome and found that fatty alcohol production can be increased to 380 mg/L [ 81 ].…”
Section: Resultsmentioning
confidence: 99%
“…Tong, Y. et al developed a CRISPR system for actinomycete genomes that can efficiently and reversibly control target genes actIORF1 and actVB [ 80 ]. Cai, P. et al, edited Pichia pastoris genome and found that fatty alcohol production can be increased to 380 mg/L [ 81 ].…”
Section: Resultsmentioning
confidence: 99%
“…The combined expression of ScRad51 , ScRad52 , and ScSae2 significantly improved the HR rate of O. polymorpha ( Gao et al, 2021 ). On the contrary, ScRad51/Rad52 expressed in P. pastoris ( Cai et al, 2021 ) and S. stipitis ( Cao et al, 2018 ) had no distinct improvement in HR efficiency, but overexpression of endogenous Rad51 and Rad52 resulted in higher HR activity of P. pastoris ( Cai et al, 2021 ). Presumably, the mechanism of DSB repair is mysterious and complex, the choice of proper genes and the expression strength of these genes are important to increase HR efficiency, which is essential for efficient operation of the multiple genes simultaneously in non-conventional yeasts.…”
Section: Discussionmentioning
confidence: 99%
“…A combination of NADH kinase and aspartate aminotransferase may be more promising. Of course, the overexpression of these functional genes needs to find a suitable site, that is, an integration site that has little effect on the metabolism of A. niger after the site is knocked out, such as neutral sites (Cai et al, 2021 ). To quickly realize the multiple genetic manipulations of related genes in aconidial A. niger , a method is also mentioned in this paper, using AfpyrG-tagged cas9 plasmid for homologous recombination (Fig.…”
Section: Discussionmentioning
confidence: 99%